Gula dan Kesehatan: Kajian Terhadap Dampak Kesehatan Akibat Konsumsi Gula Berlebih - Sinaga, Janes; Sinambela, Juita Lusiana; Purba, Beni Chandra; Pelawi, Stepanus (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Excessive sugar consumption has become a major public health problem in recent times. The purpose of this review article is to provide a comprehensive picture of the harmful effects of sugar consumption on human health. The review includes an analysis of various studies and scientific findings conducted over the past few decades. This review examines the impact of excess sugar consumption on a range of health outcomes, including obesity, diabetes, heart disease, and cancer. The study also addresses the mechanisms underlying the link between sugar consumption and the development of such health problems. The results of this study showed that excessive sugar consumption significantly increases the risk of various serious diseases and health problems. That's why it's important for individuals and society to reduce sugar consumption and eat healthier. This overview provides a better understanding of the importance of being aware of the adverse health impacts of sugar consumption and lays the groundwork for efforts to effectively address this issue.